Sharpening Kindergarten Children’s Creativity by Learning Numbers Through Plasticine - Nurhikmah, Nurhikmah; Purnamasari, Nur Indah (Yayasan Abdurrauf Cendekia Nusantara, 2025)
This study aims to explore the effectiveness of using plasticine as a learning medium for numbers in kindergarten (TK) Wulil Amri Mannurukki. The research employs a qualitative approach with a descriptive method to observe and analyze the impact of plasticine use on the cognitive development, creativity, and fine motor skills of children aged 4–6 years. The study subjects consist of 20 kindergarten children in Gowa Regency who had never used plasticine in number learning. The results indicate that the use of plasticine significantly enhances children's understanding of numerical concepts, with 85% of the subjects able to recognize and form numbers 1–10 after the intervention. Additionally, plasticine stimulates children's creativity, as evidenced by their ability to further create with numbers and related objects. Fine motor skills also show positive development, marked by improved ability to manipulate plasticine and perform other motor activities. This study concludes that plasticine is an effective and enjoyable learning medium, particularly at TK Wulil Amri Mannurukki, as it not only strengthens children's numerical understanding but also hones their creativity and fine motor skills. Therefore, plasticine is worth considering as an alternative learning medium for numbers in early childhood education